The optimal solution of drainage the excess free groundwater in a part of Akkar plain using mathematical modeling - سليمان, مراد; شريف بدر حايك,; غطفان عبد الكريم عمّار, (Latakia University Journal -Engineering Sciences Series, 2023)
Groundwater modeling is one of the methods used in hydrogeological sciences because of its importance in predicting future effects of different stresses, and put appropriate solutions to groundwater drainage problems, and managing its sources. It was observed that the level of free groundwater rose in Akkar Plain, and in some areas, it has reached the point of drowning. Therefore, it was necessary to search for the optimal solution to overcome this phenomenon. A mathematical model was built that simulates the hydrogeological conditions of the free aquifer for a part of Akkar Plain with an area of 15 km², using the (GMS) program, based on the monthly data measured in year 2015. It was proposed to drill 23 wells for vertical drainage, with a discharge ranging between (200-400) m³/d for each well. The results indicated an increase in investment from wells to (7590) m³/d, and a decrease in groundwater levels that ranged between (1-3) m, with the flow maintaining its direction towards the Mediterranean.